Evolution of a solid electrolyte interphase enabled by FeNX/C catalysts for sodium-ion storage. Issue 2 (12th January 2022) - Xia, Huicong; Zan, Lingxing; Qu, Gan; Tu, Yunchuan; Dong, Hongliang; Wei, Yifan; Zhu, Kaixin; Yu, Yue; Hu, Yongfeng; Deng, Dehui; Zhang, Jianan
Abstract : The reversible conversion reaction of a SEI was enabled by FeN X catalysts, which provided novel avenues for designing anode materials. Furthermore, a large number of spin-polarized electrons were stored in the already-reduced Fe species. Abstract : The structure and chemical engineering of a solid electrolyte interphase (SEI) play a vital role in rechargeable batteries. The underlying correlation between the properties of the enhanced sodium (Na) ion storage and SEIs in metal–nitrogen (MN X ) platform electrodes was not revealed during charging and discharging cycles. Herein, the capacity enhancement of FeN X /C anodes was first clarified by employing in situ temperature-dependent Nyquist plots and ex situ X-ray photoelectron spectroscopy. It was evidenced that physiochemical evolution of the SEI and surface carbonaceous materials made a significant contribution to the improved sodium storage performance through the following three mechanisms: (1) FeN X catalyzed the reversible conversion of SEIs, beneficial to the storage and release of extra Na ions, (2) a large number of spin-polarized charges were stored on the surface of the reduced Fe species, and (3) the carbon delivered additional capacity through the surface-capacitive effects. As a result, the FeN X /C anode provided a high capacity of 217 mA h g −1 after 1000 cycles at 2000 mA g −1 . Therefore, the FeN X species catalyzed the reversible conversion reaction of SEIs, which contributed novel avenues to the design of conversion-type electrode materials.